Road and Airfield Pavement Technology Proceedings of 12th International Conference on Road and Airfield Pavement Technology, 2021 - Pasindu, H. R.; Bandara, Saman; Mampearachchi, W. K.; Fwa, T. F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume gathers the latest advances, innovations, and applications in the field of pavement technology, presented at the 12th International Conference in Road and Airfield Pavement Technology (ICPT), hosted by the University of Moratuwa, Sri Lanka, and held on July 14-16, 2021. It covers topics such as pavement design, evaluation and construction, pavement materials characterization, sustainability in pavement engineering, pavement maintenance and rehabilitation techniques, pavement management systems and financing, transportation safety, law and enforcement related to pavement engineering, pavement drainage and erosion control, GIS applications, quarry material assessment, pavement instrumentation, IT and AI applications in pavement. Featuring peer-reviewed contributions by leading international researchers and engineers, the book is a timely and highly relevant resource for materials scientists and engineers interested in pavement engineering.
Chapter 1: A Brief Review: Application of Recycled Polyethylene Terephthalate as a Modifier for Asphalt Binder -- Chapter 2: A Comparative Investigation on the Effectiveness of a Wax and a Resin Based Curing Compound an an Alternate of Water Curing for Concrete Pavement Slab -- Chapter 3: A Framework for Selecting Safety Treatments for Rural Roads -- Chapter 4: A Review on Utilization of C & D Waste for Road and Pavement Construction in the International Context and Applicability of the Findings to Sri Lanka -- Chapter 5: Alkali Activated Black Cotton Soil Using Class F Fly Ash and Limestone Powder with Areca Fiber Reinforcement -- Chapter 6: An Assessment of the Polishing Behaviour of Road Surfacing Aggregates in Sri Lanka -- Chapter 7: Analysis and Numerical Simulation of Semi-Circle Bending Fatigue Crack Propagation of Asphalt Mixture -- Chapter 8: Analysis of Skidding Potential and Safe Vehicle Speeds on Wet Horizontal Pavement Curves -- Chapter 9: Applicability of Gneiss Based Mineral Aggregates for the Use in High Friction Surface Treatment in Terms of Polishing Characteristics -- Chapter 10: Applications of Molecular Dynamics in Asphalt Pavement Mixture Studies.
Keywords: Building materials; Transportation engineering; Traffic engineering; Materials -- Analysis; Buildings -- Design and construction; Building Materials; Transportation Technology and Traffic Engineering; Materials Characterization Technique; Building Construction and Design; Pavements -- Design and construction -- Congresses; Runways (Aeronautics) -- Congresses